Formação, saberes e práticas de professoras/es egressas/os do programa escola da terra da Universidade Federal de Uberlândia - Silva, Michele Maria da (2024)
This thesis presents the results of research developed in the Postgraduate Program in Education at the Federal University of Uberlândia (PPGED/UFU), in the line of Knowledge and Educational Practices. The study's research theme is the Escola da Terra Program – UFU and Rural Education, addressing issues of training, knowledge and educational practices. The research investigates how teachers who graduated from the I Course of Improvement in Rural Education of the Escola da Terra Program – UFU (2018-2019) evaluate and reflect on their teaching practice based on the studies, knowledge and experiences developed during the Course, considering consideration of a set of educational policies aimed at training teachers who work in rural schools. The general objective was to analyze how teachers, working in schools in the rural area of Triângulo Mineiro, perceive and evaluate their pedagogical practice in the Course. As specific objectives, the following were defined: I - analyze the history of the constitution of rural education in Brazil and educational organizations in the countryside; II - understand and analyze the historical process of Rural Education in Brazil, highlighting advances and setbacks; III - present and contextualize the I Improvement Course in Rural Education, developed at UFU; IV - identify and analyze the training, knowledge and pedagogical practices of teachers from rural schools, graduates of the I Improvement Course in Rural Education - Escola da Terra Program -UFU (2018 – 2019). The methodological approach is anchored in qualitative research (Flick, 2004). As a strategy, documentary research was used (Ludke and André, 1986) to access data related to the Course, laws, instructions and related standards. Oral History (Meihy, 2002; Portelli, 1997) was used to access and analyze the impact of the course on the training, knowledge and pedagogical practices of teachers. The thesis is organized into four sections. From the research it was concluded that the Course contributed significantly to the continued training of graduates, promoting the development of teaching autonomy and pedagogical practices connected with the reality of students in rural schools.